Exploring teachers' perspectives on digital media utilization for innovative science and social studies learning in elementary schools - Sabrina Budi; Ivayuni Listiani; Candra Dewi; Endang Sri Maruti; Wasilatul Murtafiah (Universitas PGRI Madiun, 2025)
This study explores teachers' perspectives on the use of digital media as an innovation in IPAS (Science and Social Studies) learning in elementary schools. The development of digital technology has accelerated the transformation of learning processes; however, its implementation at the elementary school level still faces various challenges, particularly in schools with limited infrastructure. Employing a descriptive qualitative approach, this study was conducted at SDN Nglanduk 01 through in-depth interviews with the principal and four teachers, complemented by classroom observation. Data were analyzed thematically through data reduction, data display, and conclusion drawing. The findings indicate that teachers hold predominantly positive perspectives toward digital media use, viewing it as an effective tool for enhancing student enthusiasm and motivation in IPAS learning. Teachers have utilized various digital tools, including PowerPoint presentations, instructional videos, Google Classroom, and EduCode. The primary challenges encountered include unstable internet connectivity and limited technological devices. In response, teachers demonstrated adaptive and innovative attitudes through participation in technical training and self-directed learning. These findings carry significant implications for policy development: systematic digital competency programs and equitable technology infrastructure are essential prerequisites for sustainable integration of digital media in elementary IPAS learning.